Mythodrama Group Psychotherapy Method, ıts Basic Principles and Practical Use with Children and Adolescents - Korinteli, Revaz; Siradze, Nino (European Scientific Journal, ESJ, 2017)
The article describes a Group Psychotherapy method – Mythodrama, its theoretical background, basics principles and practical use with children and adolescent.